Study and simulation of the electric field-induced spin switching in PZT/NiFe/CoFe nanostructured composites - Thi Nguyen, Minh Hong; Pham, Thanh Tien; Van La, Nam; Chen, Soo Kien; Nguyen, Tiep Huy (Universiti Putra Malaysia, 2023)
In this work, we have studied the electric field-induced spin switching in the PZT/NiFe/CoFe nanostructured composites by sputtering ferromagnetic layers on a horizontal polarized piezoelectric PZT substrate. The electric field-induced change in the magnetization orientation was investigated systematically using a vibrating sample magnetometer and analytical simulations. The results revealed that electric field applications could indirectly control the magnetic spin orientations. Moreover, the magnetization change depends not only on the electric field but also on the direction of the electric field applying against the magnetic field. The images of magnetic moment orientations under various electric field applications are modeled by the Monte Carlo and NMAG simulations. In particular, a critical electric field of Ecr ≈ 300 kV/cm, which makes a 90o spin switching, was determined. These results are proposed to offer an opportunity for random access memory applications.